Circular RNA ciRS-7 triggers the migration and invasion of esophageal squamous cell carcinoma via miR-7/KLF4 and NF-κB signals. Issue 1 (2nd January 2019) - Huang, Hairong; Wei, Lei; Qin, Tao; Yang, Nan; Li, Zhongdong; Xu, Zhiyun
ABSTRACT: Esophageal squamous cell carcinoma (ESCC) is one of the most prevalent and deadly cancers worldwide, especially in Eastern Asia. It has been indicated that circular RNAs (circRNA) are the key regulators in the development and progression of human cancers. We therefore evaluated the expression and regulation effects of ciRS-7 on the progression of ESCC, which is a recently identified circRNA and acts as a natural competing endogenous RNA. The expression of ciRS-7 was significantly increased in the ESCC tissues and cells as compared with their corresponding controls. In vitro study showed that ciRS-7 can promote the migration and invasion of ESCC cells. Over expression of miR-7, one of well-known targets of ciRS-7, can attenuate ciRS-7 induced invasion of ESCC cells and over expression of matrix metalloproteinase 2 (MMP2). The expression of stem cell marker Kruppel-like factor-4 (KLF-4), which has been reported as the target of miR7, increased significantly in ciRS-7 transfected ESCC cells. Knockdown of KLF-4 also attenuated over expression of ciRS-7 induced cell invasion. In addition, BAY 11–7082, the inhibitor of NF-κB, partially reversed ciRS-7 induced cell invasion. Mechanically studies indicated that ciRS-7 increased the expression of p65 via increasing the phosphorylation of IKK-α. Collectively, our present study revealed that ciRS-7 can trigger the migration and invasion of ESCC cells via miR-7/KLF4 and NF-κB signals. Targeted inhibition of ciRS-7 might be a potential approach for ESCC treatment.